The Differences in Knowledge About Breast Self-Examination Between Adolescent Girls and Women of Childbearing Age in Lingkar Timur Public Health Center Bengkulu - Nova Oktavia; Yesenia Yoelanda Febri (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2019)
Breast cancer is a type of cancer that is most commonly found in women. Breast cancer can be found early with conscious examination, clinical examinations, and examination of mammography. Early detection of breast cancer can give a life expectancy. The purpose of this study was to analyze the differences in knowledge about breast self-examination between adolescent girls in high school and women of childbearing age in the area public health centers of Lingkar Timur, Bengkulu City. The type of research used in this study was Pre Experiment using the One Shot Postest Only design. The population in this study is the overall high school student, amounting to 208 and women of childbearing age amounting to 50. the number of samples in this study consisted of 50 high school students and 50 women of childbearing age,so that the total sample amounted to 100 people. The sampling technique uses the Stratified Random Sampling technique for high school students and the total population of women of childbearing age.This study uses primary data that is processed in univariate and bivariate. This research was conducted in May-June 2016. The results of univariate analysis showed that of the 50 female students, 48 (96%) had sufficient knowledge about examining their own breasts while from 50 women of childbearing age 29 people (58%) had good knowledge. The results of bivariate analysis using the Mann-Withney test obtained significant (p = 0,000) 0.05, which means that there are significant differences between the knowledge of adolescent girls and women of childbearing age. It is expected that young women will take part in health screening activities in the working area of public health centers such as Posbindu and for women of childbearing age to increase their awareness of early detection related to women's reproductive health. Keywords: adolescent girls, breast self-examination, knowledge, women of childbearing age